Effects of multilevel metacognition on group performance and regulation in collaborative learning - Qiao, Lifang; Zhao, Wei; Liu, Fengjuan; Xu, Xiaoqing; Tao, Jinhong (Frontiers in Psychology, 2024)
Group metacognition is a key to effective collaboration. However, existing research mainly focuses on individual metacognition in collaborative learning, and some studies focused on interpersonal metacognition. The understanding of group metacognition is limited. Less attention has been paid to how multilevel metacognition, including individual metacognition, interpersonal metacognition, and group metacognition, functions. There is also less research on whether group metacognition influences collaborative learning through other levels of metacognition. To investigate the emergence of multilevel metacognition among learners with varying achievement and its effects on group performance and regulation patterns, this study employed traditional and process analyses to examine how the distribution and interactions of multilevel metacognition influence group performance and group regulation. The study revealed that in collaborative learning, group metacognition exerts the most significant influence on group performance compared to other metacognitive levels, such as individual metacognition and interpersonal metacognition. Specifically, the study identified three collaborative achievement categories by judging the degree of collaborative benefit based on individual preparation and group performance: H_T category, EF category and L_T category. The H_T and EF categories performed better and developed more group metacognition, while the L_T category exhibited poorer performance and less group metacognition. Other levels of metacognition contribute to form group metacognition, with multilevel metacognitive interactions elucidating the mechanisms of group metacognition. This study provides practical insights for multilevel metacognition and offers guidance for collaborative learning interventions, specifically those targeting group metacognition.